SAFEGUARDING INDONESIA'S CASSAVA INDUSTRY: CRITICAL RESPONSE TO SLCMV'S ADVANCE IN SOUTHEAST ASIA - Setiawan, Andree Wijaya; Kusuma, Asista Fatma (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
Sri Lankan Cassava Mosaic Virus (SLCMV) has emerged as a significant threat to cassava production in Southeast Asia since its initial detection in Cambodia in 2015, with recent outbreaks in Vietnam and Thailand and its first detection in Australia in 2024. This viral disease, transmitted by the whitefly Bemisia tabaci and infected planting materials, poses a substantial risk to Indonesia's cassava industry. Studies from affected countries demonstrate yield losses of 16-33% and starch content reductions of 22-38% in infected plants. This review analyzes SLCMV's current status and potential impacts on Indonesian cassava production and proposes management strategies based on regional experiences. We identify critical risk factors, including widespread vector presence and informal planting material exchange networks. Recommended preventive measures include strengthening quarantine systems, implementing enhanced surveillance programs, developing rapid diagnostic capabilities, and establishing clean seed certification systems. Our findings emphasize the urgent need for coordinated action to protect Indonesia's cassava industry from this emerging pathogen.